Analisis Morfofonemis Prefiks dalam Percakapan Dialog pada Buku Sekkar Assre' 4 - Ayunda Putri Nazarrina; Annisa Dallilatul Hasanah; Muhamad Ipnu Hasan; Hasan Suaedi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
The Madurese language, which is used by the Madurese ethnic community both on Madura Island and outside the island, has significant dialect diversity. The mobility of the Madurese people and interaction with the Javanese language on the island of Java resulted in a mixture of dialects, which influenced the formation of new vocabulary through morphophonemic processes. This research aims to analyze the affixation process in Madurese, especially the use of the prefixes {-e} and {-pa} in the Sekar Assre’ 4 textbook. In this research, the prefixes {-e} and {-pa} are analyzed based on form, function , and its meaning in the formation of verbs, adjectives and nouns. The research uses a qualitative descriptive approach with listening and listening methods, as well as data analysis techniques such as drop and replace. The research results show that the prefix {-e} and its allomorphs (e-, epa-, eka-) function to form passive verbs and adjectives, while the prefix {pa-} functions to form nouns, especially those related to certain professions or activities . It is hoped that this research can contribute to understanding the morphological structure of the Madurese language, especially related to the role of the prefixes {-e} and {-pa} in everyday communication and in learning Madurese in schools.